A size-dependent tensorial plasticity model for FCC single crystal with irradiation. (February 2015) - Xiao, Xiazi; Song, Dingkun; Xue, Jianming; Chu, Haijian; Duan, Huiling
Highlights: A unified size-dependent tensorial plasticity model for irradiated FCC single crystal is developed. Irradiation effect and size effect are considered simultaneously. The spatial-dependent interaction between dislocations and SFTs is considered as a tensorial form. A critical crystal size can be predicted by the proposed model. Abstract: In this paper, effects of irradiation damage and crystal size on the mechanical behaviors of FCC single crystals are explored. By treating the spatial dependent interaction between dislocations and irradiation-induced stacking fault tetrahedrons (SFTs) as a tensorial form and taking into account the influence of dislocation source limitation at submicron (∼100 nm to ∼1 μm), a unified size-dependent tensorial plasticity model for irradiated single crystals is developed. The feasibility and accuracy of this model are well validated by comparing numerical results with corresponding experimental data. It is found that (1) the yield strength of unirradiated FCC copper increases with the decrease of crystal size, which mainly attributed to the mechanism shifting from dislocation forest strengthening to dislocation source limitation strengthening. (2) For large crystal copper, the yield strength increases with the amount of irradiation, which is attributed to the increase of irradiation-induced SFTs and enhancement of dislocation–defect interaction. The phenomenon of yield dropping is observed when the irradiation is strong. (3) The competition between the irradiation effect and size effect induces the existence of a critical crystal size. Below the critical size, the yield hardening is controlled by size effect. Otherwise, it is controlled by irradiation effect. Furthermore, the proposed model can easily predict this critical crystal size, which may provide a quick guideline to distinguish different hardening mechanisms regarding different crystal sizes.